Integrating cultural contexts into mathematics: effects of culture-based worksheets on students’ mastery of geometric transformations - Khairunnisa, Ika Aulia; Mairing, Jackson Pasini; Sudirman, Sudirman; Rodríguez-Nieto, Camilo Andrés (Polyhedron International Journal in Mathematics Education, 2025)
The integration of cultural elements into the learning process, particularly in mathematics, served as a strategic approach to create a contextual and engaging classroom environment. The use of Student Worksheet played a significant role in enhancing students’ comprehension of the subject matter and improving their academic performance. This research aimed to examine the effect of implementing culture based worksheet featuring the Mandau Talawang Dance of the Dayak Tribe in Central Kalimantan on students’ learning outcomes in the topic of geometric transformations. The research employed a quasi-experimental design, specifically using the one group pre-test and post-test design. Quantitative methods were used to analyze the data, applying statistical tests such as the shapiro-wilk test, the paired sample t-test, and the N-Gain Score. The participants consisted of 15 ninth grade students. The findings indicated that the data followed a not normally distributed, with significance levels of 0.013 for the pre-test and 0.002 for the post-test. The average N-Gain score showed a notable improvement in learning outcomes, reaching a high category score of 0.7829. Furthermore, the hypothesis testing using the Wilcoxon Signed Rank Test  confirmed the acceptance of H1, with a significance value of 0.000 (p < 0.05), demonstrating that the culture based worksheet had a statistically significant positive effect on students’ learning outcomes. Integrating culture-based worksheets into classroom mathematics instruction fostered students' awareness of local cultural heritage, enhanced their mathematical abilities, and improved their learning outcomes.